Clinical analysis of prenatal ultrasound diagnosis of fetal cardiovascular malformations in the first and second trimesters of pregnancy: A CARE-compliant article. Issue 33 (August 2019) - Han, Bing; Li, Ying; Tang, Yi; Qu, Xueling; Wang, Fen; Song, Haibo; Xu, Yinhui
Abstract : Abstract: Fetal cardiovascular malformations is widely focused and screened, but the accuracy of screening is not satisfactory. In this study, we compared the types of congenital heart malformation, accompanying diseases and fetal outcomes in the first and second trimesters of pregnancy to clarify the advantage of early screening. From January 2013 to June 2018, 230 fetuses were diagnosed with congenital heart malformations using ultrasound method in Qilu Hospital of Shandong University, and divided into 2 groups:the first trimester fetuses (group A) and the second trimester fetuses (group B). In addition, we collected and organized medical data of 347 cases diagnosed with congenital heart disease during 1998 to 2005 (group C). We compared the spectrum of congenital heart disease, associated comorbidities and outcome of fetuses diagnosed with congenital heart disease. There were differences in the types and incidence of cardiac malformations between the first and second trimesters of pregnancy. The number of cases of non-cardiac malformation, congenital heart disease with single ventricular circulation, fetal intrauterine death and premature pregnancy termination was significantly lower in the late stage (group A and group B) than that in the early stage (group C). More patients were screened for trisomy 21, 18, 13 syndromes and Turner syndrome in group A than group B ( P <.001). More fetuses with a 22q11 deletion were screened in group B than group C. Early pregnancy screening using ultrasound diagnosis is very important for fetuses with congenital heart disease.